Managing Practical Work in Secondary Schools Science Education: An Assessment of Teachers’ Practices - Baraka Sanjito; Denis Hyams-Ssekasi (SEAQIS Journal of Science Education, 2026)
This paper examined how science teachers manage practical work in middle secondary schools in Tanzania and how they design, prepare, implement, assess, and evaluate laboratory work. A descriptive survey design with classroom-structured observations was used. Questionnaires and observation checklists were used to gather data on 64 science teachers, and SPSS was used to analyse the data using descriptive statistics. The results showed that the strongest element was the implementation of practical work: 100% of the observed teachers could explain the steps of a procedure step-by-step, and 83.3% could relate the practical activities to the theoretical ones. Conversely, 33.3% of teachers consistently provided safety instructions and encouraged inquiry-based learning, and 41.7% used formative assessment strategies during practical sessions. In general, there were higher scores on practical implementation (75%) than on practical assessment (65.5%), indicating an imbalance in the administration of laboratory learning. The research also found that although teachers had high procedural competence, the safety practices, inquiry facilitation, and formative assessment were weak, restricting the efficacy of practical work. The results indicate the need for specific professional training, better laboratory staffing, and administrative support to facilitate safe, inquiry-based, and assessment-driven practical science teaching in public Tanzanian secondary schools.